Dialektalne cechy fonetyczne i morfologiczne oraz ukraińska leksyka somatyczna w słowniczkach Ilki Magury Матеріялы до словаря і сборничокъ словъ и выраженій чисто- народныхъ до русского словаря - Skurzewska, Agata (Studia Ukrainica Posnaniensia, 2022)
The aim of the article is to present the results of an analysis of the phonetic and morphological layers of Ukrainian lexis from glossaries and the characteristics of the somatic terminology collected by the author. Since the collected material came from Żółkiew district, which belongs to the area of the Transnistrian dialect, the phonetic and morphological features of this dialect are presented in those constructions in particular. The lexicological analysis of this publication will help to determine whether the lexical material presented there is confirmed in dialects or in the normative layer of the Ukrainian language. It will also help to describe the scale of this confirmation. The majority of lexemes that are somatic terminology and names of diseases are confirmed to dialects of the Ukrainian language, while some word units are presented in the modern literary language.